Distribution of the Q192R polymorphism of the paraoxonase 1 gene in a population of the district of Junín (Junín region, Peru) - Carranza Alva, Elizabeth (2017)
Objective: Paraoxonase 1 (PON1), an esterase associated with high-density lipoproteins (HDL), has several polymorphisms: the PON1 Q192R polymorphism (coding region) is responsible for variations in the paraoxonase activity of the enzyme. The PON1 192R allele is considered a risk factor for developing cardiometabolic disorders in some populations. The aim of the present study is to determine the distribution of the PON1 Q192R polymorphism and its association with the lipid profile and APO A1 in an Andean population. Materials and methods: A descriptive, cross-sectional study involving 79 healthy adults (26 males and 53 females), residents of the district of Junín at 4105 m.a.s.l. The PCR/RFLP technique was used for the analysis of the PON1 Q192R polymorphism. The serum values of the lipid profile and APO A1, and the paraoxonase and arylesterase activities of the enzyme were determined. Results: The distribution of the genotypes for PON1192 was QQ 13.9%, QR 45.6% and RR 40.5%, and the most frequent allele was 192R 63%. The baseline and stimulated paraoxonase activities were different based on their genotypes, while the esterase activity of the enzyme was not influenced by the polymorphism. On the other hand, no association was found between the PON1 Q192R polymorphism and the lipid profile and APO A1. Conclusions: The high prevalence of the PON1 192R allele among the studied population probably indicates an important role in the development of cardiometabolic diseases.